2018
DOI: 10.2503/hortj.okd-132
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Food Functionality of a Local Pungent Radish “Izumo Orochi Daikon” ‘Susanoo’ by Introduction of a Colored Root Character

Abstract: Purple and red colored root characteristics were introduced to a local pungent radish "Izumo orochi daikon" 'Susanoo', and several characteristics including food functional components were evaluated. The root and leaf phenotype, the pigment composition, the isothiocyanate and soluble solids contents, and the 1,1-diphenyl-2picrylhydrazyl (DPPH) radical scavenging activity in the root were investigated. These characteristics were compared between the mass selection breeding lines of purple, red roots and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Purple color implies the presence of anthocyanins, and, according to the study of Reference [51], 60 different compounds were detected and identified as cyanidin glucosides. Most of the anthocyanins are present in acylated forms of cyanidin glucosides which increase their stability, and they could be easily used as natural colorants in functional foods [7,50,238,239], while root extracts may also exhibit beneficial health effects against gastric injuries [240].…”
Section: Other Root Vegetablesmentioning
confidence: 99%
“…Purple color implies the presence of anthocyanins, and, according to the study of Reference [51], 60 different compounds were detected and identified as cyanidin glucosides. Most of the anthocyanins are present in acylated forms of cyanidin glucosides which increase their stability, and they could be easily used as natural colorants in functional foods [7,50,238,239], while root extracts may also exhibit beneficial health effects against gastric injuries [240].…”
Section: Other Root Vegetablesmentioning
confidence: 99%
“…Purple color implies the presence of anthocyanins, and, according to the study of Reference [44], 60 different compounds were detected and identified as cyanidin glucosides. Most of the anthocyanins are present in acylated forms of cyanidin glucosides which increase their stability, and they could be easily used as natural colorants in functional foods [7,43,238,239], while root extracts may also exhibit beneficial health effects against gastric injuries [240].…”
Section: Other Root Vegetablesmentioning
confidence: 99%